Experimental Analysis of Inkjet Printed Multi Metal Oxide Photoelectrodes for Water Splitting Applications - Karabudak, Engin; Tekneci, Gülsüm Efsun; Adem, Umut (Izmir Institute of Technology, 2020)
Recently, scientific research studies focus on renewable energy solutions as well as energy efficiency in managing the upcoming climate crisis which manifests itself in the form of global warming. However, the chaotic nature of renewable energy sources caused energy storage technologies to gain importance. In addition to battery technologies consisting of lithium and post-lithium ion, zinc-air, nickel-zinc and lead-acid; artificial photosynthesis products such as hydrogen and methanol also show superiority in transportation. Especially hydrogen fuel is in the leading position with gravimetric energy density of approximately 140 MJ/kg. In this study, the experimental procedure is conducted and analyzed to produce cost-effective multi-metal oxide catalysts at high speed and efficiency with a combinatorial approach using inkjet printing technology to obtain hydrogen by splitting water. Considering the abundancies in nature, especially nickel, cobalt, iron, manganese, copper and chromium salts were preferred to obtain oxide derivatives. Inkjet printing experiments were conducted with the printer provided by Sağlık İzleme Sistemleri A.Ş.. The precision of the printed layers was examined and compared with the literature values. In cases involving differences from the literature value, possible causes are emphasized and solutions are suggested. Problems in transition from single metal oxide printed layers to more complicated multi-metal oxide prints have been examined and solutions have been proposed. As a result, this experimental study is aimed to provide foresight for large-scale (photo)electrocatalyst production with the utilization of inkjet printing.

Günümüzde küresel ısınma şeklinde kendini gösteren, yaklaşmakta olan iklim krizinin yönetilmesinde enerji verimliliğinin yanısıra yenilenebilir enerji çözümlerine odaklanılmaktadır. Bununla birlikte yenilenebilir enerji kaynaklarının kaotik yapısı enerji depolamanın daha fazla önem kazanmasına yol açmıştır. Lityum ve post-lityum iyon, çinko-hava, nikel-çinko ve kurşun-asitten oluşan pil teknolojilerine ek olarak gravimetrik enerji yoğunluğu bu teknolojilerden çok daha fazla olan, hidrojen ve metanol gibi yapay fotosentez ürünleri buna ek olarak taşınabilirlik konusunda da üstünlük göstermektedir. Özellikle hidrojen yakıtı yaklaşık olarak 140 MJ/kg'lık gravimetrik enerji yoğunluğuyla lider konumdadır. Bu çalışmada suyun ayrıştırılmasıyla hidrojen eldesi için mürekkep püskürtme baskı teknolojisi kullanılarak kombinasyonel yaklaşımla düşük maliyetli çoklu metal oksit katalizörlerinin yüksek hız ve verimde üretilmesi için deneysel prosedür incelenmiş ve analiz edilmiştir. Doğada bulunma sıklığı göz önüne alınarak oksit türevlerinin eldesi için özellikle nikel, kobalt, demir, mangan, bakır ve krom tuzları tercih edilmiştir. Mürekkep püskürtme baskı denemelerinin tümü Sağlık İzleme Sistemleri A.Ş. tarafından sağlanan yazıcıyla yapılmıştır. Baskıların hassasiyetleri incelenmiş olup literatür değerleriyle karşılaştırma yapılmıştır. Literatür değerinden farklılıklar içeren durumlarda olası nedenler üzerinde durulmuş ve çözüm yolları önerilmiştir. Tekli metal oksit baskılardan daha komplike olan çoklu metal oksit baskılara geçişte yaşanan problemler incelenmiş ve çözüm önerileri getirilmiştir. Sonuç olarak yapılan deneysel çalışmanın mürekkep püskürtme baskı kullanılarak büyük ölçekli (foto)elektrokatalizör üretimine yönelik öngörü sağlaması hedeflenmiştir.
Su Ayrıştırma Uygulamaları için Mürekkep Püskürtme Baskılı Çoklu Metal Oksit Fotoelektrotların Deneysel Analizi
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 2020
Includes bibliographical references (leaves: 58-63)
Text in English; Abstract: Turkish and English
Keywords: Energy storage; Inkjet printing; Renewable energy sources